Biliary complications after transcatheter arterial chemoembolization for hepatocellular carcinoma - Yoon Suk Lee; Kyung-Ah Kim (Society of Gastrointestinal Intervention, 2020)
Transarterial chemoembolization (TACE) is considered an effective procedure for liver malignancy. Although the majority of TACE related complications can be treated conservatively, appropriate therapeutic interventions, such as percutaneous/endoscopic drainage or partial hepatectomy, might be needed in cases of signs of severe infection and/or progressive biloma. Therefore, we herein report a case of TACE induced biliary complications which were treated with a multi-disciplinary approach; intrahepatic progressive biloma was treated with percutaneous drainage, intrahepatic bile duct stricture was treated by endoscopic balloon dilation and plastic stent placement.